Respiratory and functional tests in the assessment and prognosis of patients with chagas disease - Melo de Morais, Nickson; Costa de Morais Leonez, Lara Candice; Mesquita de Andrade, Cléber; Oliveira Pereira, Wogelsanger; Gurgel Cosme do Nascimento, Ellany; Veríssimo Fernandes, José; Medeiros Bezerra, Christiane; Araújo de Medeiros Fernandes, Thales Allyrio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
Chagas disease causes an important impact on cardiorespiratory system, functional and working capacity of the patient. Performing a functional assessment on these individuals becomes essential, since the impact of physical limitation is an important factor that is related with other life domains, such as risk of cardiovascular events in a brief period and risk of death. The goal of this work was to perform a literature review to present the evaluative and prognostic value of main valid respiratory and functional tests in patients with Chagas disease, as well as their applicability and reproducibility. A literature search was performed from 1981 to 2020 in Scielo, Pubmed/Medline, Science Direct, Scopus and Web of Science databases. Only complete studies published in English, Portuguese or Spanish were analyzed which specifically discussed the respiratory and functional tests used in patients with Chagas disease. In total, 544 articles were retrieved of which 35 were eligible. The main functional tests approached were Cardiopulmonary Exercise Testing, Incremental Exercise Testing and Six-Minute Walk Test. Several studies show themselves as useful markers for predicting quality of life, mortality and functional impairment, in addition to other patients’ characteristics. Several tests can be used to assess the respiratory and functional impact to patients’ health, as well as its relationship with important domains of their lives. KEY WORDS: Chagas disease; Chagas cardiomyopathy; exercise test; respiratory function tests; prognosis.